2003
DOI: 10.1007/s00238-003-0475-z
|View full text |Cite
|
Sign up to set email alerts
|

End-to-side neurorrhaphy of sensory nerves

Abstract: One century passed before end-to-side neurorrhaphy was rediscovered, and now it finds more frequent use in clinical practice. Experimental studies have improved our understanding of the underlying mechanism and its potential. However, still discussed is whether reinnervation by end-to-side neurorrhaphy works as well in sensory nerves as in motor nerves. The digital nerves are sensory nerves and therefore an ideal model to investigate this question. Two cases of successful sensory reinnervation by end-to-side n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…A detailed overview concerning the selection process is shown in Figure 1. Those remaining 2,997 digital nerve repairs provided the basis for further analysis (Table 2 [3, 25, 34–48], Table 3 [8–12], Table 4 [3, 25, 36, 40, 43, 48–57], Table 5 [14, 5864], Table 6 [36, 45, 56, 6568], Table 7 [19, 37, 64, 6971], and Table 8 [25, 7277]). Some case reports, which were excluded from the meta-analysis to lower heterogeneity regarding the given sensory recovery outcomes, are nevertheless shown in Tables 2–8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed overview concerning the selection process is shown in Figure 1. Those remaining 2,997 digital nerve repairs provided the basis for further analysis (Table 2 [3, 25, 34–48], Table 3 [8–12], Table 4 [3, 25, 36, 40, 43, 48–57], Table 5 [14, 5864], Table 6 [36, 45, 56, 6568], Table 7 [19, 37, 64, 6971], and Table 8 [25, 7277]). Some case reports, which were excluded from the meta-analysis to lower heterogeneity regarding the given sensory recovery outcomes, are nevertheless shown in Tables 2–8.…”
Section: Resultsmentioning
confidence: 99%
“…An epineural window serves as a connection point between the two nerves, while the extent of the perineural fenestration remains controversial [7]. The end-to-side nerve coaptation can be used to repair severed digital nerves, mostly caused by previous hand injuries, when direct tension-free coaptation is not possible [8–12]. …”
Section: Introductionmentioning
confidence: 99%
“…The study of Voche and Quattara (2005) included nine patients operated on for digital nerve lesions and one for a common digital nerve injury. Frey and Giovanoli (2003) reported two clinical cases of terminal-lateral suture of the digital nerve, one of which was completed in 1995 and seems thus to be the first clinical application of this procedure. A further four cases have been recently reported by Landwehrs and Bruser (2008) which used a clinical evaluation based on the two-point discrimination test and the Semmes-Weinstein monofilament test.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of experimental [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] as well as clinical [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] studies have shown that end-to-side nerve coaptation is able to induce collateral sprouting from donor nerve’s axons, allowing for significant repopulation of the distal nerve stump.…”
Section: Introductionmentioning
confidence: 99%